2020
DOI: 10.1016/j.ijnss.2020.07.007
|View full text |Cite|
|
Sign up to set email alerts
|

Unhealthy aging? Featuring older people in television food commercials in China

Abstract: Objectives Advertising messages can affect the public as a risk or protective factor for socially disadvantaged groups, and they may reflect how characters reflect perceptions are perceived in a society. This study aimed to investigate how older people are portrayed in televised food commercials from the approach of a healthy aging perspective in contemporary Chinese society. Methods All televised advertising in the Ad Topic archive were screened against inclusion and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Media depictions of aging and older adulthood are attracting interest across diverse fields, for example, cultural gerontology (Wellin, 2018 ; Ylänne, 2021 ), media and communications (Ayalon et al, 2020 ; Sedick & Roost, 2011 ; Xi et al, 2020 ), political science (Zhuravskaya et al, 2020 ), and health and wellbeing (Avers et al, 2011 ; Jiao & Chang, 2020 ; Robinson & Callister, 2008 ). This body of research documents how media influences cultural attitudes, norms, and values; plays a key role in discourses and stereotypes of old age and promotes a cultural or social imaginary of later life (Ayalon et al, 2020 ; Dahmen & Cozma, 2009 ; Sedick & Roos, 2011 ; Ylänne, 2021 ).…”
Section: Media Depictions Of Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Media depictions of aging and older adulthood are attracting interest across diverse fields, for example, cultural gerontology (Wellin, 2018 ; Ylänne, 2021 ), media and communications (Ayalon et al, 2020 ; Sedick & Roost, 2011 ; Xi et al, 2020 ), political science (Zhuravskaya et al, 2020 ), and health and wellbeing (Avers et al, 2011 ; Jiao & Chang, 2020 ; Robinson & Callister, 2008 ). This body of research documents how media influences cultural attitudes, norms, and values; plays a key role in discourses and stereotypes of old age and promotes a cultural or social imaginary of later life (Ayalon et al, 2020 ; Dahmen & Cozma, 2009 ; Sedick & Roos, 2011 ; Ylänne, 2021 ).…”
Section: Media Depictions Of Agingmentioning
confidence: 99%
“…However, in tension with these more negative stereotypical portrayals, other research suggests that, increasingly, media stereotypes construct later life as being possible (even ‘normal’) to have youthful agency, health, wealth, leisure, and be sexually, socially, and bodily able (Marshall & Rahman, 2015 ). Katz ( 2005 ) has suggested that media stereotypes depict the older adulthood life stage as “growing older without aging” (p. 188)—a kind of “agelessism” (Jiao & Chang, 2020 , p. 571), while Sandberg and Marshall ( 2017 ) found prevalent stereotypes of aging as being “hetero-happy” (p. 3). Such messages reproduce a stereotype that aging is a personal choice; a product of lifestyle behaviors; and that a happy long life is positioned in relation to heterosexual coupledom, children, and grandchildren.…”
Section: Media Depictions Of Agingmentioning
confidence: 99%
“…Older adults are under-and misrepresented in the media (cf. Bai et al, 2016;Jiao & Chang, 2020), and they are often stereotypically perceived as 'incompetent, frail, outdated and wretched' (Li, 2021). Recent research has shown that older adults are active users of social media, and their lively self-representation not only challenges the stigma of old age but also helps promote modernisation in China (Li, 2017(Li, , 2021.…”
Section: Ageing and Intimacy In The Era Of Technologisationmentioning
confidence: 99%
“…Although old age is associated with both positive and negative traits, the exhibition of ageist attitudes has been more widely documented. Extensive researches show how mainstream society stereotypes the older population as more negative (incompetent, frail and dependent) than positive (warm, experienced and functioning), and the stereotypes are pervasive and persistent (Bai et al, 2016; Cuddy et al, 2005; Harwood et al, 1996; Jiao and Chang, 2020). The preference of media for reporting negative stereotypes of the elderly leads to a media image of the group as incompetent, frail, outdated and wretched.…”
Section: Mediated Image Of Chinese Older Adultsmentioning
confidence: 99%